Step distribution of Yb filling fraction during microstructural evolution in skutterudites - Jing Mei; Zheng Yao; Shuya Zhu; Dongli Hu; Ying Jiang; Juanjuan Xing; Hui Gu; Lidong Chen (Journal of Advanced Ceramics, 2019)
Abstract To achieve a better material for thermoelectric power generation device, filled skutterudite Yb0.3Co4Sb12 samples were fabricated by melting–quenching–annealing–spark plasma sintering (SPS) method. Two sets of samples, before and after SPS, were investigated. In both the two sets of samples, the average grain size of the samples increases monotonously with the increase of annealing time, while Yb filling fraction firstly increases and then decreases. Yb not filling into the skutterudite remains at the grain boundaries in the form of Yb2O3 after SPS, which could be quantified by the spatially difference method of energy dispersive spectra. Step distribution of Yb filling fraction was observed in the samples annealed for 1 h, which was caused by the microstructural evolution from the peritectic phases to the skutterudite phase. The sample annealed for 3 days and SPS sintered possesses the maximum value of Yb filling fraction 0.249 and the maximum ZT value of 1.24 at 850 K. These results are helpful to better understand the microstructural evolution and Yb filling behavior in skutterudite materials.